PENGARUH ETOS KERJA DAN INSENTIF TERHADAP KINERJA KARYAWAN PT PARIT PADANG GLOBAL CABANG JAKARTA 3 - Doni Wibowo; Muhammad Harri (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2023)
The objective this research is to analyze the influence of work Ethics and incentives to employee perfomance at PT Parit Padang Global Cabang Jakarta 3. The method for collecting of data used observation and questionnaires.The sampling method with the probability sampling by 80 respondents. The result of this research concluded thar descriptive view the most of respondents give perception with strong agree to work ethics conditions, incentives and also employee performance. Furthermore, based on simple regression method, Score, and Observation. The factors of discipline, morale, and turnovers already good. The work ethics and incentives give influence as positive and significant to employee work perfomance. The recommendations of this research, the company has been to maintaining and improving work ethics especially on employee perfomance, work relationship, and mental readiness of employee, discipline, motivational leadership.